2017
DOI: 10.1007/s10531-017-1297-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinship appeals and conservation social marketing

Abstract: Increasing environmental problems and the need to obtain public support to help address them make effective appeals in conservation fundraising campaigns indispensable. However, social marketing messages based on data, characteristics of focal species, selfinterest, and moral responsibility tend to work best on targeted, and so limited, audiences. As conservation organizations reach out to broader audiences, they will require strategies that appeal to more potential donors. This paper argues that use of kinshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…It is not clear if support for legal protection for basking sharks is related to the ‘charisma’ or ‘likeability’ of the species or a belief that it is economically valuable. Research has found that ‘cute’ and charismatic ‘flagship’ species tend to get more conservation support (Karaffa, Draheim & Parsons, 2012; Qirko, 2017). However, the lack of a significant difference between support for legal protections for ‘basking sharks’ or just ‘sharks’ may imply that survey respondents were overall receptive to conservation, regardless of the charisma of the species.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear if support for legal protection for basking sharks is related to the ‘charisma’ or ‘likeability’ of the species or a belief that it is economically valuable. Research has found that ‘cute’ and charismatic ‘flagship’ species tend to get more conservation support (Karaffa, Draheim & Parsons, 2012; Qirko, 2017). However, the lack of a significant difference between support for legal protections for ‘basking sharks’ or just ‘sharks’ may imply that survey respondents were overall receptive to conservation, regardless of the charisma of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Social scientists have also observed trends toward greater biophilia that are driving more effective conservation policy (Manfredo et al 2020). Enlarging species coverage and scientific content to address shark roles in marine ecosystem health as well as supplying critical-anthropomorphic portraits that personalize these nonhuman animals (Whitley et al 2021, p. 840;Qirko 2017) can contribute to their conservation by enhancing human empathy. In like manner, reporting on new scientific discoveries, such as white shark preferences, which coincide with associations that suggest the existence of friendships (Schilds et al 2019;Solstice Media 2019), can work to underscore individuality in a positive light and tap biophilic trends.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most effective appeals in animal conservation is the use of kinship symbolism because characterizing nonhuman species and nonliving resources as kin to humans promotes a willingness to contribute to conservation (Qirko, 2017). Thus, anthropomorphism, or the attribution of human characteristics to animals and even the natural world, is recognized as a valuable tool for conservation (Root-Bernstein et al, 2013).…”
Section: Biodiversity Loss and Importance Of Conservationmentioning
confidence: 99%